Analisis Kruskal-Wallis Terhadap Kemampuan Numerik Siswa - Andi Quraisy; Wahyuddin Wahyuddin; Nur Hasni (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2021)
This study aims to determine the differences in the numerical abilities of students from 4 classes, namely classes A, B, C, and D. The population in this study were students of class VII SMP Muhammadiyah 1 Makassar with a total sample of 57 students. The data collection technique used a numerical ability test instrument, then the data obtained were analyzed using descriptive analysis and Kruskal-Wallis nonparametric analysis. The results of the descriptive analysis obtained that the average value of the numerical abilities of students in grades A, B, C, and D was not much different, namely 76.13; 78.4; 76.57; 77.23. Meanwhile, the results of the Kruskal Wallis analysis showed that there was no significant difference in the grades of A, B, C, and D numerical abilitiesKeywords: Mann-Whitney test, Non-parametric test,  Problem Based Learning Model